Effectiveness of Oral Stimuly Cold Therapy (Popsicle) on Thirst Perception in Postoperative Patients: A Systematic Review - Wati Melawati; Debie Dahlia; Sri Yona; Liya Arista (Indonesian Journal of Global Health Research, 2025)
Thirst after surgery is commonly experienced by patients, with prevalence reaching 70-80% within the first 24 hours postoperatively. This condition, often overlooked in clinical practice, can impact the quality of patient recovery. Popsicle, as a form of oral stimuli cold therapy, offers an effective solution to alleviate this complaint. Objective: This study aims to evaluate the effectiveness of popsicle therapy in reducing thirst and improving comfort and the quality of recovery in postoperative patients.Methodology: A systematic review approach was used by analyzing five scholarly articles based on randomized controlled trials (RCT) and quasi-experimental designs from 2018–2024. The keyword search used was popsicle OR "oral stimuli cold therapy" OR ice therapy AND postoperative period OR postoperative AND thirst. A total of 486 articles were found, and 5 were analyzed. Articles were selected based on Joanna Briggs Institute (JBI) criteria to assess methodological quality. Discussion: The use of popsicle has been proven to reduce the intensity of thirst, with higher effectiveness compared to other non-pharmacological methods such as room-temperature water or cold sprays. The addition of menthol to popsicles enhances patient comfort and satisfaction, as well as reduces symptoms of dry mouth and halitosis.Results: All studies indicated that popsicles, especially those containing menthol, were significantly more effective in reducing postoperative thirst. Popsicles also improved the patient's recovery experience through positive psychological effects.